2019
DOI: 10.5114/fn.2019.85938
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic effects of acrylamide on dopaminergic neurons in primary mesencephalic cell culture

Abstract: Introduction: Exposure to acrylamide is increasing worldwide as a result of its heavy use in industry and formation in carbohydrate-rich food cooked at high temperature. Despite its neurotoxicity, no studies have shown its toxic effects on dopaminergic neurons yet. Therefore, the current study was carried out to show whether acrylamide adversely affects primary cultured dopaminergic neurons. Material and methods: Acrylamide (0.001, 0.01, 0.1, 1, 2 mM) was added to two different groups of primary mesencephalic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Unlike MPP + which specifically damages dopaminergic neurons, rotenone was shown to injure other neuronal populations in primary mesencephalic cell culture. Similar results were obtained by our laboratory for some other neurotoxins like domoic acid [56] and acrylamide [57].…”
Section: Rotenone Model Of Parkinson's Diseasesupporting
confidence: 89%
“…Unlike MPP + which specifically damages dopaminergic neurons, rotenone was shown to injure other neuronal populations in primary mesencephalic cell culture. Similar results were obtained by our laboratory for some other neurotoxins like domoic acid [56] and acrylamide [57].…”
Section: Rotenone Model Of Parkinson's Diseasesupporting
confidence: 89%
“…Thymoquinone (TQ, 2-isopropyl-5-methyl-1, 4-benzoquinone, Figure 14 ) is a monoterpenoid hydrocarbon, and it is the major bioactive compound of the volatile black oil from Nigella sativa. This molecule is endowed with antioxidant and anti-inflammatory properties [ 82 ], in addition to counteracting apoptosis in primary dopaminergic cells after their treatment with 1-methyl-4-phenylpyridinium (MPP+) and rotenone [ 83 , 84 ]. Recently, it was found that TQ prevents dopaminergic neurodegeneration in a PD mouse model, activating the nuclear translocation of Nrf2 for binding to ARE.…”
Section: Natural Nrf2 Activatorsmentioning
confidence: 99%
“…Acrylamide is categorised as a neurotoxic compound, with toxic effects on the central nervous system (CNS) and peripheral nervous system (PNS), both in laboratory animals and in humans [28]. The reported symptoms of acrylamide exposure include limb numbness, muscle weakness or ataxia, and they most probably result from an inhibition of the kinesin-based fast axonal transport and alterations in the neurotransmitter levels [29][30][31]. Acrylamide binds with protein receptors rich in cysteine that are involved in the presynaptic release of the neurotransmitters, membrane reuptake, and vesicular nerve conduction, which results in disturbed synaptic transmission [32].…”
Section: Discussionmentioning
confidence: 99%